2008
DOI: 10.1016/j.neulet.2008.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Viral vector-mediated blockade of the endocrine stress–response modulates non-spatial memory

Abstract: Stress results in the release of glucocorticoids (GCs) which, at high levels, impair hippocampusdependent tasks. Estrogen is neurotrophic and can rescue stress-induced memory impairments. Here we report the use of a viral-vector to overexpress a chimeric gene (ER/GR) that converts the deleterious effects of glucocorticoids into beneficial estrogenic effects. A short immobilization stress regimen was sufficient to impair non-spatial memory. In contrast, viral vector-mediated overexpression of ER/GR in the denta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The glucocorticoid receptor (GR) and several components of its multiprotein chaperone complex have been implicated as a point of convergence for genetic, epigenetic and environmental factors shaping stress vulnerability (59). Converging data from psychiatric genetics and animal studies indicate that mechanisms affecting the stoichiometry and interactions of proteins within the GR chaperone heterocomplex profoundly influence the physiology of the hypothalamic-pituitary-adrenal (HPA) axis (1012) as well as stress coping (1318). However, how molecular regulation of GR chaperone dynamics translates into emergent neurobehavioral traits defining vulnerability or resilience is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…The glucocorticoid receptor (GR) and several components of its multiprotein chaperone complex have been implicated as a point of convergence for genetic, epigenetic and environmental factors shaping stress vulnerability (59). Converging data from psychiatric genetics and animal studies indicate that mechanisms affecting the stoichiometry and interactions of proteins within the GR chaperone heterocomplex profoundly influence the physiology of the hypothalamic-pituitary-adrenal (HPA) axis (1012) as well as stress coping (1318). However, how molecular regulation of GR chaperone dynamics translates into emergent neurobehavioral traits defining vulnerability or resilience is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…While glucocorticoids (stress-steroids) are instrumental in the chronic disease states developed after experiencing prolonged stress, they also initiate rapid behavioral responses to direct threats or acutely stressful situations (Breuner et al, 1998;Coddington et al, 2007;Moore and Miller, 1984). A majority of the neuroendocrine research into stress-steroid effects has focused on long-term genomic effects (Akama and McEwen, 2005;Carrasco and Van de Kar, 2003;Ferguson et al, 2008;Ferguson and Sapolsky, 2007;Kaufer et al, 2004;Sapolsky, 2000). However, the neuroendocrine regulation of rapid behavioral/neuronal responses to immediate threats is not yet well understood.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, approximately one-quarter of the people with Alzheimer disease have cardiovascular disease, and another quarter have diabetes [2]. Therefore, while the positive effects of certain steroid hormones on memory may be due to their direct effects on the nervous system, the increase in activity [36], along with the cardiovascular protective effects of steroids [7,36], may also play a role in sustaining improvements in memory function by maintaining blood flow to the brain, and enhancing the metabolic activity of cells in the brain, which makes them less sensitive to the activation of pathways involved in apoptosis and necrosis [37][38][39]. Previous studies have demonstrated that when there is a reduction in glucose availability to the central nervous system, any challenge (i.e., metabolic, disease related, stress-induced etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that when there is a reduction in glucose availability to the central nervous system, any challenge (i.e., metabolic, disease related, stress-induced etc.) is exacerbated [37][38][39][40]. Studies have demonstrated that E2 treatment reduces the damage that occurs as a result of a stroke [6,40,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation